2012
DOI: 10.3851/imp2419
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy and Sustained Virological Response to HCV Therapy are Associated with Slower Liver Fibrosis Progression in HIV–HCV-Coinfected Patients: Study from the Anrs Co 13 Hepavih Cohort

Abstract: Our findings show that long-term ART and achieving sustained virological response in HIV-HCV-coinfected patients are both significantly associated with lack of increase in LS over a 33-month period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 38 publications
2
24
0
3
Order By: Relevance
“…Earlier ART in individuals co-infected with HCV is associated with slower progression of hepatic fibrosis and reduced risk of liver disease progression [30,31]. Our results showed that patients with HCV co-infection had a higher mortality compared to those who had only HIV infection.…”
Section: Discussionmentioning
confidence: 66%
“…Earlier ART in individuals co-infected with HCV is associated with slower progression of hepatic fibrosis and reduced risk of liver disease progression [30,31]. Our results showed that patients with HCV co-infection had a higher mortality compared to those who had only HIV infection.…”
Section: Discussionmentioning
confidence: 66%
“…Large clinical trials comparing pretreatment and posttreatment liver biopsies have previously shown improvements in inflammation as well as in fibrosis scores following HCV SVR. A [9,19,20] recent meta-analysis of six studies with a total of 443 HCV-monoinfected cirrhotic patients showed that SVR was associated with almost a three-fold higher chance of cirrhosis regression, as shown by liver biopsy [21].…”
Section: Discussionmentioning
confidence: 98%
“…Hazardous alcohol use exacerbates HCV-related liver disease through increased HCV viral replication, toxic effects on the liver, and indirectly via effects on ART adherence and decreased HCV treatment eligibility[4751]. In addition, alcohol use among PLWH co-infected with HCV is associated with faster liver fibrosis progression, while sustained virological response to HCV therapy is associated with slower liver fibrosis progression[52]. HCV treatment is rapidly evolving with higher treatment success rates and easier treatment regimens, however alcohol use remains a potential contraindication to HCV treatment among PLWH[53].…”
Section: Discussionmentioning
confidence: 99%